Clays and Clay Minerals, Vol. 60, No. 4, 411–419, 2012. - Yamagishi, Akihiko; Sato, Hisako (The Clay Minerals Society, 2012)
Attempts at optical resolution and asymmetric syntheses using smectite clay minerals are described. Use of the method was prompted by the discovery that the saturated adsorption of a tris(chelated) metal complex, [Ru(1,10-phenanthroline)3]2+, by Na-montmorillonite depended heavily on the stereochemical properties. The pure enantiomer was adsorbed by cation exchange at negative surface sites of the clay mineral, while the racemic mixture was adsorbed to two times excess of the cation exchange capacity. The chelate takes a uniform orientation on a clay mineral surface due to the matching between the molecular symmetry and the two-dimensional network of a phyllosilicate layer. On a clay mineral surface covered with the enantiomeric chelates, a vacant space capable of chiral discrimination was generated. Based on this, an ion-exchange adduct of smectite and the chiral chelate was used as an adsorbent for separating racemic mixtures or selectively producing either one of the optical isomers.
Stereochemistry And Molecular Recognition On The Surface Of A Smectite Clay Mineral
gsccm60407-yam.pdf -- 1,230KB
Keywords: Periodicals; Geology; Asymmetric Syntheses; Chiral Sensing; Circular Dichroism; Clay-modified Electrodes; Electric Dichroism; LB Films; Molecular Chirality; Optical Resolution; Stereoselectivity; Tris (1,10-phenanthroline)metal(II)